Diagnosis and prevention of hyponatremia at an ultradistance triathlon - Speedy, D. B.; Rogers, I. R.; Noakes, T. D.; Thompson, J. M.; Guirey, J.; Safih, S.; Boswell, D. R. (Clinical Journal of Sport Medicine, 2000)
OBJECTIVE: To evaluate a method of medical care at an ultradistance triathlon, with the aim of reducing the incidence of hyponatremia. DESIGN: Descriptive research. SETTING: New Zealand Ironman triathlon (3.8 km swim, 180 km cycle, 42.2 km run). PARTICIPANTS: 117 of 134 athletes seeking medical care after the triathlon (involving 650 race starters). INTERVENTIONS: A prerace education program on appropriate fluid intake was undertaken. The number of support stations was decreased to reduce the availability of fluid. A body weight measurement before the race was introduced as a compulsory requirement, so that weight change during the race could be included in the triage assessment. An on-site laboratory was established within the race medical tent. MAIN OUTCOME MEASURES: Numbers of athletes and diagnoses, including the incidence of symptomatic hyponatremia (defined as symptoms of hyponatremia in association with a pretreatment plasma sodium concentration [Na] < 135 mmol/L); weight changes; and changes in [Na]. RESULTS: The common diagnoses in the 117 athletes receiving attention were exercise-associated collapse (27%), musculoskeletal complaints (26%), and dehydration (12%). There was a significant reduction in the number of athletes receiving medical care for hyponatremia, from 25 of the 114 athletes who received care in 1997 (3.8% of race starters) to 4 of the 117 athletes who received care in 1998 (0.6% of race starters). Mean weight change among athletes in the 1998 race was -3.1 kg, compared with -2.6 kg in 1997. CONCLUSION: A preventive strategy to decrease the incidence of hyponatremia, including education on fluid intake and appropriate placement of support stations, was associated with a decrease in the incidence of symptomatic hyponatremia.